MENANGGULANGI KEBAKARAN DIMUSIM KEMARAU - Ageng saepudin kanda S; Zaeni muhamad fauzi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Fires in the dry season are one of the natural disasters that often occur in Indonesia. These fires can be caused by various factors, including human activity, negligence, and natural factors. Human activities, such as burning forests to clear land, throwing cigarette butts carelessly, and lighting campfires without supervision, are the most common factors causing fires. Fires in the dry season can cause various losses, both in terms of material, environmental and social aspects. Preventing fires in the dry season can be done in various ways, including increasing public awareness about the dangers of fire and how to prevent them, enforcing the law against perpetrators of forest and land arson, increasing preparedness to face fires, by providing adequate facilities and infrastructure, preventing and controlling efforts. fire. Fires in the dry season need to be taken seriously to reduce the risk of fires and the impacts they cause.